Human Development Index, Poverty and Gross Regional Domestic Product: Evidence from Malang, Indonesia - Dwi Wulandari; Bagus Shandy Narmaditya; Putra Hilmi Prayitno; Suryati Ishak; Lutfi Asnan (Faculty of Economics, State University of Jakarta., 2019)
This study aimed at analyzing the relationship between human development index, poverty level and gross regional domestic product in Malang Regency in Indonesia. This research was initiated by the poverty level which shows a moderate level in Malang Regency and how its impact on gross regional domestic product after the Development of Southern Cross Lane (JLS) in Malang. The study applied an explanatory research using time series data between 2014 and 2018. For the analysis, Vector Error Correction Model (VECM) was applied to understand the relationship between variables both in the short-term and in the long-term. The findings showed that in the short-run both variables have a negative correlation with gross regional domestic product. Meanwhile, in the long-run, human development index has a negative relationship to gross regional domestic product, whilst poverty variables positively affects gross regional domestic product.